2005
DOI: 10.1002/bem.20112
|View full text |Cite
|
Sign up to set email alerts
|

A numerical evaluation of SAR distribution and temperature changes around a metallic plate in the head of a RF exposed worker

Abstract: The 1998 International Commission for Non-Ionising Radiation (ICNIRP) Guidelines for human exposure to radiofrequency (RF) fields contain a recommendation to assess the potential impact of metallic implants in workers exposed up to the allowable occupational field limits. This study provides an example of how numerical electromagnetic (EM) and thermal modelling can be used to determine whether scattered RF fields around metallic implants in workers exposed to allowable occupational ambient field limits will co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…In certain (plane wave) cases, the distance between the implant and the skin surface may match the wavelength in tissue so that constructive interference occurs in the surface layers (e.g., distance ¼ l T /4) [McIntosh et al, 2002McIntosh and McKenzie, 2003]. This may cause elevated SAR in the surface [McIntosh et al, 2002McIntosh and McKenzie, 2003;Anderson et al, 2004].…”
Section: Surrounding Tissuesmentioning
confidence: 96%
See 2 more Smart Citations
“…In certain (plane wave) cases, the distance between the implant and the skin surface may match the wavelength in tissue so that constructive interference occurs in the surface layers (e.g., distance ¼ l T /4) [McIntosh et al, 2002McIntosh and McKenzie, 2003]. This may cause elevated SAR in the surface [McIntosh et al, 2002McIntosh and McKenzie, 2003;Anderson et al, 2004].…”
Section: Surrounding Tissuesmentioning
confidence: 96%
“…In the context of RF dosimetry, analyses of near fields apply to devices used in the proximity of body such as mobile and radio phones, and far field analyses can be regularly applied to the exposure to base stations (except near them). Most of the reviewed implant studies [Johnson and Guy, 1972;Hocking et al, 1991;Fleming et al, 1992;McIntosh et al, 2002McIntosh et al, , 2004McIntosh and McKenzie, 2003;Anderson et al, 2004] concern the far field exposure, but a few [Cooper and Hombach, 1996;Tuppurainen, 2001;Virtanen et al, 2005] have also concentrated on implants exposed in the near fields. The motivation for the far field studies comes partly from the occupational exposure of RF workers, who may encounter high exposure levels at work.…”
Section: Near and Far Fieldsmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerical SAR simulations of human head with metallic plate were performed before, [40] and metal plate dimensions were one third of the applied RF wavelength, which resulted in resonance peaks at the absorbed electric field. In our study, the dimensions of the implant were much smaller than the RF exposure wavelength, which, in turn, did not result in resonance peaks in electric field distribution.…”
Section: Histopathological Analysismentioning
confidence: 99%
“…Previous in vitro studies have shown that tissue ambustion can be caused by the temperature of a metal plate at frequencies near 900 MHz and 27 MHz [7]. However, in vitro studies of radio frequency (RF) electromagnetic fields showed that the metal implants caused little risk using 1800 MHz [8] and 2450 MHz [9,10] microwave radiation. Furthermore, shortwave diathermy, also a high frequency electrotherapy, was clinically applied by some doctors and therapist to the cure and rehabilitation in injuries bone with surgical implanted metal [11,12].…”
Section: Introductionmentioning
confidence: 99%